2009
DOI: 10.1111/j.1365-2494.2008.00676.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological development and nutritive value of herbage in five temperate grass species during primary growth: analysis of time dynamics

Abstract: In a 2-year field experiment, morphological development and measures of the nutritive value of herbage for livestock during primary growth in Meadow foxtail, Tall oatgrass, Cocksfoot, Perennial ryegrass and Yorkshire fog were investigated. All measured variables were affected significantly by both species and sampling date, and their interaction (P < 0AE001), in the period of primary growth. Changes with time in mean stage weight for Meadow foxtail and Cocksfoot were different from the other species due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 19 publications
3
10
0
Order By: Relevance
“…The values were consistent with a range of forage nutritive quality measurements presented elsewhere (e.g. Dalley et al, 1999;Ominski et al, 2006;Hegarty et al, 2007). These constant values had a lower influence on model outputs than NDF due to their lower absolute values or gradients.…”
Section: Enteric Methane Production Modellingsupporting
confidence: 88%
See 1 more Smart Citation
“…The values were consistent with a range of forage nutritive quality measurements presented elsewhere (e.g. Dalley et al, 1999;Ominski et al, 2006;Hegarty et al, 2007). These constant values had a lower influence on model outputs than NDF due to their lower absolute values or gradients.…”
Section: Enteric Methane Production Modellingsupporting
confidence: 88%
“…The non-significant explanatory variables were removed from the full models as all terms were found to reduce Akaike's information criterion (AIC). The relative influence of each term on the model likelihood was assessed by comparing the AIC of the current model with that of a simplified model with the terms deleted until the AIC ceased to decline (Crawley, 2013;Richards, 2005). Temperature and rainfall could not be included together in the LME models because these variables were shown to covary strongly (P < 0.001); either temperature or rainfall was included in the full models based on minimising the AIC.…”
Section: Statisticsmentioning
confidence: 99%
“…The following year, only switchgrass was investigated and then it did not exhibit a linear morphological developmental pattern. Čop et al. (2009) have used the scale of Sanderson (1992) to study the time course of weighted mean values, by weight, for five temperate grass species for two years and found that the time curves were close to linearity for tall oatgrass ( Arrhenatherum elatius (L.) Beauv.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, trampling can accelerate plant litter decomposition, while promoting the grass-livestock-soil balance. Grazing intensity impacts new tissue regeneration, delays plant lignification, thereby increasing the CP, EE, and DMD, while reducing NDF and ADF concentrations, which will help meet the nutrient requirements of grazing livestock ( National Research Council, 2007 ; Čop et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%